Fretting wear mapping: the influence of contact geometry and frequency on debris formation and ejection for a steel-on-steel pair - Warmuth, A.R.; Shipway, P.H.; Sun, W. (Royal Society, 2015)
This paper examines the influence of contact geometry and oscillation frequency in a steel cylinder-on-steel flat fretting contact, with contact geometry being varied via the cylinder radius. Fretting frequency did not significantly impact the wear behaviour for more-conforming contacts, but did so for less conforming contacts where at high frequency, the wear rate is 50 % of that observed for low frequency fretting. It is proposed that frequency and contact conformity fundamentally control wear behaviour through influence of both the debris type and the retention or ejection of that debris from the contact. The debris type (either oxide or metallic) is influenced by fretting frequency (which controls the interval between asperity contacts), and by contact conformity (which controls the distance that oxygen has to travel to fully penetrate the contact). Debris retention within the contact is promoted by higher fretting frequencies (the associated higher contact temperature promotes debris agglomeration and sintering in the contact) and by higher contact conformity (which acts as a physical barrier to debris egress). Maps are presented which categorize the observed behaviour and outline a phenomenological framework by which the basic physical processes which influence fretting behaviour can be understood.